POLITIK HUKUM PERLINDUNGAN PEREMPUAN PEKERJA DOMESTIK DI INDONESIA - Wardani Amnesti, Sheila Kusuma (Pusat Studi Gender UIN Maulana Malik Ibrahim Malang, 2024)
AbstractFemale domestic workers still dominate the numbers as victims of rights violations. Female domestic workers are not only vulnerable to having their rights as workers violated, but also experience discriminatory treatment and even sexual harassment. The purpose of this article is to look at the background to the formulation of government policy lines in an effort to ensure the fulfillment of the rights of women workers in the domestic sector. This research is normative juridical research using a statute approach. The results of this research show that the Domestic Workers Protection Bill has the characteristics of a responsive legal product which reflects society's sense of justice, especially for domestic workers who are dominated by women. On the other hand, in the theory of legal protection, the Indonesian government is obliged to ratify ILO Convention 189 concerning the Protection of Domestic Workers and as soon as possible pass the Domestic Workers Protection Bill. This article is a form of thought contribution in efforts to uphold human rights, especially the rights of women workers.Keywords: Female domestic workers; Legal Policy; Legal ProtectionAbstrakPerempuan pekerja domestik masih mendominasi angka sebagai korban pelanggaran hak- hak. Perempuan pekerja domestik tidak hanya rentan dilanggar haknya sebagai pekerja, namun mendapat perlakuan diskriminatif hingga pelecehan seksual. Tujuan dari artikel ini adalah melihat latar belakang penyusunan garis kebijakan pemerintah dalam upaya menjamin terpenuhinya hak-hak pekerja perempuan di sektor domestik. Penelitian ini merupakan penelitian yuridis normative dengan menggunakan pendekatan statute approach. Hasil penelitian ini menunjukkan bahwa RUU Perlindungan Pekerja Rumah Tangga memiliki karakteristik produk hukum yang responsif dan telah mencerminkan rasa keadilan masyarakat khususnya bagi pekerja rumah tangga yang didominasi oleh perempuan. Disisi lain dalam teori perlindungan hukum, pemerintah Indonesia wajib melakukan ratifikasi Konvensi ILO 189 tentang Perlindungan Pekerja Rumah Tangga dan sesegara mungkin mengesahkan RUU Perlindungan Pekerja Rumah Tangga. Tulisan ini sebagai bentuk kontribusi pemikiran dalam Upaya menegakkan hak-hak asasi manusia khususnya hak pekerja perempuan.Kata Kunci: Perempuan Pekerja Domestik; Politik Hukum; Perlindungan Hukum